Loyalitas Dan Mentalitas Abraham Dalam Mengikuti Panggilan Allah - Pangarepo, Baltasar Junias; Tri Wardoyo, Gregorius (Borneo Review, 2023)
The presence of a chosen nation that began with God's covenant with Abraham, also began with God's promise to Abraham about descendants who would become Abraham's heirs in the future. Of course this begins with God's promise to the descendants of Eve who will be the savior (Genesis 3:15). So that there is a development of God's statement in a specific and representative manner with the presence of Abraham's descendants. When God appeared to Abraham after arriving in Shechem, the promise of descendants was repeated (Genesis 12:7). This means that the presence of heirs will determine the blessing of the nations. In the development of the theological world, there is a common misconception that the Old Testament (OT) does not have a mission mandate and that the OT is a book dedicated only to the Jewish people and Jewish history. However, this view does not match the claims made by the Old Testament itself. If you pay close attention to the beginnings of the Old Testament then it would be a mistake to judge that the Old Testament lacked a mission challenge. The message in the earliest chapters of Genesis is that there is a universal and global audience. Didn't God deal with "all the peoples of the earth" when God acted in saving at the three incident points, namely the fall of mankind, the flood event and the tower of Babel in Genesis 1-11? God directs the great message of salvation to all mankind (Genesis 3:15; 9:17; 12:1-3). The presence of a chosen nation that began with God's covenant with Abraham, also began with God's promise to Abraham about descendants who would become Abraham's heirs in the future. Of course this begins with God's promise to the descendants of Eve who will be the savior (Genesis 3:15). So that there is a development of God's statement in a specific and representative manner with the presence of Abraham's descendants. When God appeared to Abraham after arriving in Shechem, the promise of descendants was repeated (Genesis 12:7). This means that the presence of heirs will determine the blessing of the nations. In the development of the theological world, there is a common misconception that the Old Testament (OT) does not have a mission mandate and that the OT is a book dedicated only to the Jewish people and Jewish history. However, this view does not match the claims made by the Old Testament itself. If you pay close attention to the beginnings of the Old Testament then it would be a mistake to judge that the Old Testament lacked a mission challenge. The message in the earliest chapters of Genesis is that there is a universal and global audience. Didn't God deal with "all the peoples of the earth" when God acted in saving at the three incident points, namely the fall of mankind, the flood event and the tower of Babel in Genesis 1-11? God directs the great message of salvation to all mankind (Genesis 3:15; 9:17; 12:1-3).